Bibliometric Analysis: Marginal Productivity and its Relevance Towards Modern Labor Wage Determination - Nanda Setia; Rozalinda Rozalinda; Testru Hendra (AL-IQTISHADIYAH : EKONOMI SYARIAH DAN HUKUM EKONOMI SYARIAH, 2025)
This study aims to analyze the development of scientific publications on Marginal Productivity and its relevance to determining modern labor wages during the period 2020 to 2025 using a bibliometric approach. Data was obtained from Scopus basic data by downloading article metadata in RIS and CSV formats, then processed using VOS viewer software with a minimum number of keywords of 5 out of 2,893 keywords, 207 of which met the threshold to produce three types of visualizations, namely network visualization, overlay visualization, and density visualization. The results showed that there were 558 publications related to the topic during the six years of observation with a downward trend from 113 articles in 2020 to 68articles in 2025. Network visualization revealed that "wage determination" was the main node that had the strongest connection with other themes, such as wage gap, labor policy, gender disparity, productivity, and macroeconomic dynamics. The network structure forms several thematic clusters reflecting research focuses, including wage inequality, human capital, labor productivity, monetary policy, and the impact of globalization on the labor market. Meanwhile, the overlay visualization shows a shift in research focus from macro issues, such as monetary policy and industrial structure in the early period, to more social and justice-based themes, such as gender inequality, minimum wages, and worker protection in more recent years. These findings demonstrate that the study of wage determination is developing in a multidisciplinary and dynamic manner, with a growing emphasis on inclusivity, social inequality, and evidence-based labor policy in the context of the modern economy